Genetic differentiation at the inter specific level of Rhyzopertha dominica from Southern India using RAPD molecular markers - Naik, R Harischandra; Mohankumar, S; Rajan, T Sonai; Chandrasekaran, S (Indian Journal of Plant Protection, 2020)
Molecular markers play a major role in analyzing the genetic variation and diversity of lesser grain borer, Rhyzopertha dominica (Fab.), a key stored grains insect pest for developing and implementing an effective integrated pest management (IPM) strategy. The present study was conducted to assess the genetic differentiation of R. dominica collected from three southern states of India viz., Tamil Nadu, Andhra Pradesh and Karnataka using 20 RAPD primers. All the RAPD primers were consistently amplified across the populations tested and showed the polymorphism level of 54.54 to 100 per cent. Phylogenetic analysis of R. dominica populations formed distinct clusters with this the populations from Thanjavur, Tirunelveli, Tiruppur, Virudhunagar, Hyderabad and West Godavari formed separate cluster from all other populations. The similarity co-efficient values showed limited genetic variation (44%) of R. dominica. This preliminary analysis of R. dominica with RAPD markers showed very limited diversity of R. dominica populations across three southern states of India. Extending the present study with the codominant DNA markers (SSR) will provide valuable information for further population genetics of this pest species and that would be helpful for the development and implement of an effective integrated pest management strategy in future.